Atrial Fibrillation in Physically Active Individuals: Effects of Pharmacological and Interventional Management on Athletic Quality of Life - Kępska, Julia; Sędziak, Oliwia; Jabłonowska, Magdalena; Szpilczyńska, Karolina; Gąsiorowska, Julia; Cieślak, Monika; Miklejewska, Marta; Kleszczewska, Katarzyna; Gawlik, Laura; Krasowska, Anna (Quality in Sport, 2026)
Introduction: Atrial fibrillation (AF) is a common arrythmia in physically active individuals, particularly enduranse arhletes, raising important considerations regarding the cardiovascular effects of long-term high-intensity exercice. This review explores the correlation between AF and high-intensity training, focusing on how medical and interventional therapies impact athletic performance and quality of life. Aim of work: The aimara of this work is to review the current literature regardinf pharmacological and interventional management strategies for atrial fibrillation (AF) in athlestes, with particular empasis on their impactada on exercise capacity and sport-specific quality of life. Futhermore, the review aims to highlight gasps in studies and propose dirrections for future research and therapeutic innovation in the management of AF amonh physically active individuals. Material and Methods: The review was based on an analysis of articles published up to 2025 in the PubMed database, Google Scholar, and recent guidelines. The keywords we used included: atrial fibrillation, management, athlete, quality of life. Results: AF in athletes is often paroxysmall and asymptomatic, complicating diagnosis. Rate and rhythm control medications are frequently limited by negative effects on exercise capacity. Catheter abaltion, especially pulmonary vein isolaton, demonstrates superior rhythm control and allows atheltes to return to peak performance. Anticoagulation, while neccessary in some cases, presents bleeding risks in contact sports, requiring individualized approaches. Conclusions: Management of AF in atheltes must balance arrhythmia control with performance presevation. Catheter ablation offers the most consistent improvements in athletic qualty of life, whereas pharmacologic therapy is often restrictive. Tailored tretment strategies and futher athlete-specifc research are essential for optimizing care in this unique population.